Novel active LiFePO4 battery balancing method based on chargeable and dischargeable capacity. (2nd February 2017) - Cui, Xiudong; Shen, Weixiang; Zhang, Yunlei; Hu, Cungang; Zheng, Jinchuan
Highlights: Chargeable and dischargeable capacities are dynamically estimated. A robust balancing method is applied to equalise battery pack in charging and discharging processes. A balancing circuit helps get the current of each cell with one extra current sensor. The balancing method increases the discharged pack capacity in aged LiFePO4 pack. Abstract: A lithium iron phosphate battery (LiFePO4 ) pack is one of the main power resources for electric vehicles and the non-uniformity of cells in the battery pack has become the bottleneck to improve the pack capacity. An active balancing method based on chargeable and dischargeable capacities, derived from the dynamically estimated state of charge (SOC) and capacity in the pack, is proposed to tackle this problem in both the charging and discharging processes. To determine the current of each cell in balancing operation, one extra current sensor is added with a chosen flyback balancing circuit. The balancing simulation of a LiFePO4 battery pack has been conducted in the moderate and severe capacity imbalance scenarios. The simulation results show that the proposed battery balancing method has better performance than the other balancing methods based on voltage or SOC in increasing the charged and discharged pack capacity in the charging and discharging process.